Electrospun and freeze-dried PCL/chitosan-gelatin bilayer dressing for enhanced wound healing - Jalili Ahmadabad, Mehdi; Janmohammadi, Mahsa; Nazemi, Zahra; Bahraminasab, Marjan; Arab, Samaneh; Nourbakhsh, Mohammad Sadegh (Carbohydrate polymer technologies and applications, 2025)
A double-layer (DL) wound dressing was developed by integrating electrospinning and freeze-drying techniques. The electrospun top layer (PCL/Cs) provided hydrophobicity and resistance to bacterial penetration. The incorporation of 5 % Cs increased the tensile strength of nanofibers from 5.4 ± 2.26 MPa to 12.9 ± 2.23 MPa. The freeze-dried bottom layer (Cs/Gel) exhibited a high swelling ratio exceeding 500 %, and compressive properties ranging from 0.35 to 1.36 MPa. The water vapor transmission rate (WVTR) for Cs-Gel single layers was within the range of 2000–2500 g/m²/day, while DL-50Cs and DL-25Cs exhibited WVTRs of 3300 ± 110 and 1993 ± 136 g/m²/day, respectively. The samples showed antibacterial activity against Staphylococcus aureus (S. aureus (Cs25-Gel75 (82 %), Cs50-Gel50 (72 %), DL-50Cs (78 %), DL-25Cs (79 %), PCL-Cs5 % (41 %)). The MTT revealed high cell viability for all samples, with DL-25Cs showing 453 ± 111 % viability after 3 days and 201 ± 12 % viability after 7 days. The scratch assay on L929 cells showed enhanced wound closure for all samples compared with the control (16 ± 11 %), Cs25-Gel75 (18 ± 6 %), Cs50-Gel50 (19 ± 10 %), DL-50Cs (21 ± 9 %), and DL-25Cs (23 ± 5 %). DL-25Cs exhibited the highest closure, indicating improved cell migration potential due to the double-layer structure. [Display omitted]